Genotype and spatial structure shape pathogen dispersal and disease dynamics at small spatial scales. Issue 3 (1st March 2014) - Tack, Ayco J. M.; Hakala, Jani; Petäjä, Tuukka; Kulmala, Markku; Laine, Anna-Liisa
Abstract : Many devastating pathogens are passively dispersed, and their epidemics are characterized by variation that is typically attributed to environmental factors. Here, by combining laboratory inoculations with wind tunnel and field trials using the wind‐dispersed pathogen Podosphaera plantaginis, we demonstrated striking genetic variation affecting the unexplored microscale (<2 m) of epidemics. Recipient and source host genotypes, as well as pathogen strain, explained a large fraction of variation in the three key dispersal phases: departure, movement, and settlement. Moreover, we found genotypic variation affecting group size of the pathogen dispersal unit, ultimately resulting in increased disease development on hosts close to the infection source. Together, our results show that genotypic variation may generate considerable variation in the rate of disease spread through space and time with disease hotspots emerging around initial foci. Furthermore, the extent of genetic variation affecting the entire dispersal process confirms that these traits may be targeted by selection.